MIMO Capacity Maximization With a Practical Model for Reconfigurable Intelligent Surfaces - Sirojuddin, Ahmad; Suryani, Titiek; Suwadi; Wirawan; Alouini, Mohamed-Slim (IEEE wireless communications letters, 2024)
Reconfigurable intelligent surface (RIS) is a cutting-edge technology projected to significantly enhance the spectrum and energy efficiency of current wireless communication systems. This letter addresses the problem of maximizing the capacity of practically modeled RIS-assisted single-point MIMO systems in which the reflective elements have inherent resistance. The solutions for the optimal power allocation and RIS phase shifts are obtained using the Newton-Raphson method and a modified gradient ascent algorithm, respectively. The numerical results show that the proposed method surpasses three benchmark systems in terms of the optimality of the achieved rate and the execution time.